Utilization of Black Soldier Fly Larvae in Restaurant Waste Management in Tanjung Ayun Sakti Village - Nadeak, Erpina Santi Meliana; Kirana, Tari Desfita; Horiza, Hevi; Simbolon, Veronika Amelia (Poltekkes Kemenkes Palu, 2025)
Background: The management of organic waste from restaurants in urban areas remains a significant environmental challenge because it contributes to pollution and increased greenhouse gas emissions. Bioconversion using Black Soldier Fly (BSF) larvae offers a promising solution for the rapid decomposition of organic waste while producing biomass products that have economic value. This study aims to evaluate the performance of BSF larvae with different initial weights (10 g, 20 g, and 30 g) in processing organic waste from restaurants. Methods: This experimental study with an observational approach used organic waste collected from restaurants in Tanjung Ayun Sakti Village. Five-day-old BSF larvae, which were cultivated under controlled conditions, were used in three treatment groups based on the initial weight of the larvae (10 g, 20 g, and 30 g). Larval performance was measured through waste reduction index, bioconversion rate, and feed conversion ratio. Results: The results showed that the waste reduction index for the use of 10 g, 20 g, and 30 g of larvae was 40.37%, 55.15%, and 59.27%, respectively. The bioconversion rate for the use of 10 g, 20 g, and 30 g of larvae is 2.96%, 6.67%, and 7.78%, respectively. The feed conversion rate when using 10 g, 20 g, and 30 g of larvae, respectively, was 33.75, 15.00, and 12.86. larvae biomass increased significantly with final yields of 267 g, 600 g, and 700 g. Conclusion: The results showed that the use of 30 g of larvae was the most effective compared to 10 g and 20 g of larvae based on the data waste reduction index, bioconversion rate, and feed conversion ratio. Overall, the significant increase in final larval biomass, reaching up to 700 g, confirms that higher larval quantities have a markedly positive impact on bioconversion efficiency and biomass productivity.